Properties of dried apricots pretreated by ultrasound-assisted osmotic dehydration and application of active coatings - Sakooei-Vayghan, Roghieh (Array, 2020)
Research background. The worldwide demand for healthy and sulphur-free dried vegetables and fruits has grown. Combined ultrasound-assisted osmotic dehydration (UOD) and application of active coatings incorporating natural preservatives represents an attractive alternative to sulphuring to preserve the sensorial and nutritional quality of dried fruits. The aim of this study is to investigate the effect of osmotic dehydration (OD) and UOD, and the use of pectin coatings (alone or with citric acid or ascorbic acid) on physical, textural and microstructural properties of hot air-dried apricots.Experimental approach. Fresh apricot cubes (1 cm3) were pretreated with either OD at 55 °C for 30 and 45 min or UOD at two ultrasonic frequencies of 25 and 35 kHz for 30 and 45 min followed by application of active coatings with pectin alone, pectin with citric acid or pectin with ascorbic acid for 10 min. All pretreated coated samples were then hot air-dried at 60 °C until a final moisture content of 20 % (wet basis) was reached. Physical (shrinkage, apparent and bulk densities), chemical (browning value and water activity) and textural properties (firmness and shrinkage), microstructure and microbial load of dried apricots were studied.Results and conclusions. Application of OD and UOD improved physical and textural properties of the dried apricots. Moreover, apparent and bulk densities, rehydration capacity of OD and UOD pretreated samples increased, while shrinkage, water activity and microbial load decreased. Firmness of UOD pretreated samples was significantly (p<0.05) lower than that of OD ones. Likewise, increasing ultrasound frequency from 25 to 35 kHz led to a significant decrease in Fmax values of dried apricots. Furthermore, coating of the processed samples with pectin and citric acid increased Fmax value and decreased rehydration capacity of dried apricots. Scanning electron microscopy of both OD and UOD samples illustrated improvement of textural properties.